2006
DOI: 10.1016/j.surfcoat.2006.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, and electrical properties of WOx(Ny) films deposited by reactive dual magnetron sputtering

Abstract: Thin films of tungsten oxynitrides were prepared by dual magnetron sputtering of tungsten using argon/oxygen/nitrogen gas mixtures with various nitrogen/oxygen ratios.The presence of even relatively small amounts of oxygen led to close-to-stoichiometric WO 3 , with little incorporation of nitrogen, therefore the films were labeled as WO x (N y ). Oxygen had a great effect not only on the composition but on the structure of WO x (N y ) films, as shown by Rutherford backscattering and x-ray diffraction, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 36 publications
(38 reference statements)
7
24
1
Order By: Relevance
“…The XRD pattern for thin films deposited at 0.040 O 2 PP shows the presence of a broad amorphous peak centered around the expected value for the (1, 11, 0) peak of Ta 2 O 5 . A similar observation of low crystallinity for refractory oxide phases was observed during reactive sputter deposition of tungsten 20 and titanium oxynitrides. 27 The observation of poorly crystalline or amorphous thin films for the N/O stoichiometries of interest is in agreement with previous reports, and as described by Cristea et al, 23 sputter deposited TaO x N y with p O 2 þ p N 2 > 0:15 Pa encourages the formation of amorphous phases, which highlights the need for an independent thermal processing step to achieve amorphous to crystalline transitions in oxynitride systems.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The XRD pattern for thin films deposited at 0.040 O 2 PP shows the presence of a broad amorphous peak centered around the expected value for the (1, 11, 0) peak of Ta 2 O 5 . A similar observation of low crystallinity for refractory oxide phases was observed during reactive sputter deposition of tungsten 20 and titanium oxynitrides. 27 The observation of poorly crystalline or amorphous thin films for the N/O stoichiometries of interest is in agreement with previous reports, and as described by Cristea et al, 23 sputter deposited TaO x N y with p O 2 þ p N 2 > 0:15 Pa encourages the formation of amorphous phases, which highlights the need for an independent thermal processing step to achieve amorphous to crystalline transitions in oxynitride systems.…”
Section: Resultssupporting
confidence: 72%
“…For N 2 PPs sufficient to introduce significant nitrogen into the films, N/O stoichiometry varies nonlinearly as a function of the ratio of N 2 and O 2 gas flow rates, highlighting the importance of careful control and calibration of the reaction gas atmosphere. 20,21,[25][26][27][28][29] Using a variable leak valve to control O 2 PP, we demonstrate the ability to carefully control O 2 PPs and fine-tune oxynitride chemistries. We further discuss a heuristic approach to rapidly obtain the optimal O 2 PP for depositing oxynitride films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the early studies have contributed extensively towards the understanding of W-N system, especially the knowledge of fundamental relationship between different parameters, such as deposition conditions and their effect on the internal stress, microstructure, and elemental concentration [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Similarly, tungsten oxides have been studied for a wide variety of electrical, optical, and energy related applications [1][2][3][4][5][6][7][8][9][10][11][12] to longer wavelengths, and concluded that the conductivity of said films is lowered with increased nitrogen content [33]. While earlier efforts were focused on either thicker coatings …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Tungsten oxide (WO 3 ) is a widely studied "chromogenic" material with interesting structural, electronic, and optical properties for utilization in many scientific and technological applications [1][2][3][4][5][6][7][8][9][10]. Among metal oxide semiconductors, WO 3 has become a focal point of interest where nanostructured and low-dimensional forms of WO 3 are beneficial for technological development.…”
Section: Introductionmentioning
confidence: 99%